“I WANT TO USE MY SUBJECT MATTER TO...”: THE ROLE OF PURPOSE IN ONE U.S. SECONDARY HISTORY TEACHER’S INSTRUCTIONAL DECISION MAKING - van Hover, Stephanie; Yeager, Elizabeth (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
In this study, we explore the instructional decision making of Charlotte, a graduate of an intensive social studies teacher education program. Charlotte articulated a sophisticated conception of historical thinking and appeared to possess exemplary pedagogical content knowledge. Her classroom practice did not incorporate the approaches to historical thinking and inquiry that were discussed in her methods course. She possessed a clear view of her purpose of history teaching, which was to impart a particular set of moral values; her practices were consistent with her purpose; and she controlled her class to accomplish that purpose. Key words: instructional decision making, history teaching, social studies, historical inquiry, document‐based instruction, methods courses, beginning teachers Dans cet article, les auteures analysent une décision pédagogique de Charlotte, diplômée d’un programme de formation à l’enseignement spécialisé en sciences humaines. Charlotte, qui a développé une conception avant‐gardiste de la pensée historique, semble posséder une connaissance exemplaire du sujet. Ses pratiques pédagogiques n’incluent pas les approches discutées dans son cours de méthodologie quant à la pensée et à la recherche historiques. Elle a une notion claire du but qu’elle poursuit en enseignant l’histoire, à savoir la transmission d’un ensemble précis de valeurs morales. Ses pratiques vont de pair avec ce but et elle contrôle sa classe de manière à atteindre son objectif. Mots clés : décision pédagogique, enseignement de l’histoire, sciences humaines, recherche historique, enseignement à l’aide de documents, cours de méthodologie, jeunes enseignants